Promoting children's health when a parent has a mental health problem: a mixed methods study of the experiences and views of health visitors and their co-workers - Louise Condon; Timothy Driscoll; Joy Merrell; Mel Storey; Amanda Thomas; Beryl Mansel; Sherrill Snelgrove (BMC, 2020)
Abstract Background Unrecognised and untreated parental mental illness is a major adverse childhood experience with potentially life-long consequences for health and wellbeing. In the United Kingdom (UK) health visitors provide a universal health promotion service to children aged 0-5 years, which includes safeguarding. This preventive work is highly relevant to policy aims of improving outcomes for children living with adverse childhood experiences, but is currently under researched. The aim of this study was to explore how health visitors promote young children's wellbeing when a parent has a mental health problem, and to co-produce strategies to improve child health outcomes. Methods A mixed methods study was conducted, consisting of a cross-sectional survey and consensus workshops in Wales, UK. In phase 1 health visitors (n = 174) responded to an online questionnaire designed to explore the nature and scope of their preventive work with families experiencing mental ill health. For phase 2 providers of health and other support services (n = 38) took part in Nominal Group Technique workshops to co-produce strategies for better joint working to protect the wellbeing of children living with parental ill health. Results We identified that health visitors routinely provide support to families where parents have a range of mental health problems, including severe mental illness. Most practice is focused on mothers with depression, and fewer respondents were confident about working with fathers. Unmet training needs were identified in relation to adult mental illness, particularly the impact upon children. Solutions to working more effectively with professional and voluntary agencies included raising awareness of professional roles and responsibilities, timely two-way communication, taking a strengths-based approach and maintaining a focus on the child. Conclusions This study provided evidence on the range of parental mental ill health encountered by health visitors and the strategies they use to protect children's wellbeing. Increasing the effectiveness of joint working is key to improving outcomes for babies and young children, including greater use of voluntary sector services. This study has implications for those who commission and provide health and welfare services for children, and adult mental health services.